Learning from Neighbors: A Comparative Policy Analysis of Tax Education Integration in the High School Curricula of Indonesia and Malaysia - Hanifah Yasin; Idris Atmaja; Iqbal Anugerah; Dian Rahayu; Muhammad Hasan; Grace Olivia Silalahi; Selma Fajic; Fitriyanti Fitriyanti; Darlene Sitorus; Harun Urrashid (Enigma in Education, 2025)
Nations across Southeast Asia are grappling with the challenge of enhancing tax compliance to fund national development. This study addresses this issue by examining the divergent policy pathways for high school tax education in two neighboring countries: Indonesia and Malaysia. While both nations recognize the importance of cultivating tax awareness among youth, their approaches to curriculum integration differ significantly. This study employed a qualitative comparative policy analysis. The research systematically examined and contrasted official policy documents from Indonesia’s Ministry of Education, Culture, Research, and Technology (Kemendikbudristek) and the Directorate General of Taxes (DJP), with those from Malaysia’s Ministry of Education (KPM) and the Inland Revenue Board of Malaysia (IRBM). The analysis focused on four key dimensions: policy rationale, curricular placement, institutional collaboration, and implementation strategy. Data was sourced from national curriculum frameworks, ministerial decrees, tax authority publications, and strategic plans issued between 2019 and 2024. A thematic analysis was conducted to identify and compare the core characteristics of each nation's approach. The analysis revealed two distinct models. Malaysia has pursued a formal, centralized integration model, embedding tax education as a mandatory topic within the Form 5 Mathematics curriculum since 2021. This ensures universal and systematic delivery by teachers. In contrast, Indonesia has adopted an emerging, decentralized model characterized by extracurricular outreach programs, such as Pajak Bertutur, led by the DJP. While Indonesia's new Kurikulum Merdeka presents significant opportunities for formal integration, its implementation remains ad-hoc and dependent on regional initiatives. Malaysia’s strategy offers a clear model of systemic integration that Indonesia could learn from. However, Indonesia’s Kurikulum Merdeka and its emphasis on project-based learning provide a unique opportunity to embed tax education more holistically as a component of civic and economic literacy, rather than solely as a mathematical exercise. The study concludes that for Indonesia to advance its tax education agenda, a more robust and operational partnership between the DJP and Kemendikbudristek is essential to transition from sporadic outreach to sustainable, curriculum-integrated education.